1985
DOI: 10.1152/ajpendo.1985.249.2.e187
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to parathyroid hormone

Abstract: The synthetic amino terminal fragment of parathyroid hormone, PTH-(1-34), is a potent coronary artery vasodilator in the dog. In the present study, using instrumented open-chest dogs, we have performed the initial characterization of this effect and showed other dose-related cardiovascular effects of the hormone. A near-maximal flow response was obtained after intracoronary injection of 0.024 nmol X kg-1 PTH-(1-34) with minor, if any, concomitant changes in mean blood pressure, contractile force, or heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…It has been known for some time that acute administration of parathyroid hormone (PTH) has vasodilatory and hypotensive effects [7, 8, 9, 10, 11, 12, 13]. Nevertheless, the blood concentration of PTH tends to be higher in hypertensive patients, even in the absence of measured differences in the plasma ionized calcium concentration [14, 15, 16, 17, 18, 19, 20, 21, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for some time that acute administration of parathyroid hormone (PTH) has vasodilatory and hypotensive effects [7, 8, 9, 10, 11, 12, 13]. Nevertheless, the blood concentration of PTH tends to be higher in hypertensive patients, even in the absence of measured differences in the plasma ionized calcium concentration [14, 15, 16, 17, 18, 19, 20, 21, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…shear stress; endothelium; nitric oxide CORONARY ENDOTHELIUM PRODUCES several vasoactive factors that are involved in the regulation of coronary vasodilatation, i.e., nitric oxide (NO), prostacyclin, endothelium-derived hyperpolarizing factor (EDHF), and parathyroid hormone-related peptide (PTHrP). Initially, it was demonstrated that intracoronary injection of synthetic parathyroid hormone (PTH), which shares structural similarities with PTHrP, evoked an increase in coronary flow in the canine heart (4,5). In a subsequent study in rat hearts, PTHrP increased coronary flow and appeared to be more potent than PTH (13).…”
mentioning
confidence: 99%
“…These findings provoked much research and several other mechanisms have since been proposed. The presence of specific receptors for PTH has been suggested (Crass et al 1985;Nickols, 1987). This view is supported by the finding that the only antagonists which inhibit PTH-induced hypotension are the synthetic analogues of PTH, bPTH (3-34) and bPTH (7-34), and then only in excess concentrations compared with the agonist bPTH (1-34) (Nickols, 1987).…”
Section: Discussionmentioning
confidence: 93%
“…Since it is the changes in CO which are of interest rather than the absolute values, selection of an arbitrary value for compliance is justified because the compliance term cancels out in the calculation of proportional change. Although a direct effect of PTH on cardiac muscle has been observed (Hashimoto, Nakagawa, Shibuya, Satoh, Ushijima & Imai, 1981), the increase in CO is probably due, at least in part to a compensatory response to the vasodilatation (Crass, Moore, Strickland, Pang & Citak, 1985;Daugirdas et al 1987). The mechanism whereby PTH produces hypotension is unresolved.…”
Section: Discussionmentioning
confidence: 99%